Atglistatin Pretreatment Preserves Remote Myocardium Function Following Myocardial Infarction. (May 2021) - Bottermann, Katharina; Granade, Mitchell E.; Oenarto, Vici; Fischer, Jens W.; Harris, Thurl E.
The pathological role of adipose derived fatty acids following myocardial infarction has long been hypothesized. However, most methods for reducing adipocyte lipolysis have significant non-adipose effects. Atglistatin, a direct inhibitor of the initial lipase in the lipolysis cascade, has been recently shown to inhibit adipose tissue lipolysis after oral administration. To explore the ability of Atglistatin to impact the pathophysiology of cardiac ischemia we performed prophylactic treatment of mice with Atglistatin for 2 days before 1-hour cardiac ischemia. After 7 days of reperfusion, hearts of Atglistatin treated mice showed significantly improved systolic pump function while infarct and scar size were unaffected. Strain analysis of echocardiographic data revealed an enhanced performance of the remote myocardium as cause for overall improved systolic function. The present study provides evidence that inhibition of adipocyte adipose triglyceride lipase (ATGL) using Atglistatin is able to improve cardiac function after MI by targeting the remote myocardium.